"Banned from the streets I have paid to use": an analysis of Australian print media coverage of proposals for passenger and night driving restrictions for young drivers. Issue 5 (3rd October 2005) - Blows, S; Ivers, R Q; Chapman, S
Abstract : Objective: To catalogue arguments that can be anticipated in public debate when passenger and night driving restrictions are being advocated. Design and setting: Frame analysis of all relevant coverage of these topics in Australian print media during the three month period between June and September 2004 when intensive debate on the topic occurred. Main outcome measures: Debating frames used in reports and commentary on passenger and night driving restrictions. Results: There were 52 relevant articles published containing seven distinct frames supporting the restrictions and six opposing them. Overall, more instances of frames supporting the restrictions were published; these mostly focused on the potential for saving lives. Opposition to the restrictions focused largely on their inappropriateness as a road safety measure as well as on the importance of young people's autonomy and freedom. Conclusions: Advocates of passenger and night driving restrictions have a number of arguments available to advance their case; however, it is important to anticipate and address possible counter arguments. Future research should address the saliency of different arguments to the public and key decision makers in government.